2022
DOI: 10.1159/000522153
|View full text |Cite
|
Sign up to set email alerts
|

Validity of Weekly Administration of Carboplatin after Carboplatin-Induced SIADH: Two Case Reports and Literature Review

Abstract: Chemotherapy-induced severe hyponatremia is a life-threatening condition. Platinum-based agents play a key role in ovarian cancer treatment but are more likely to cause hyponatremia than other anticancer agents. The optimal strategy for treating ovarian cancer in cases of severe platinum agent-induced hyponatremia remains unclear. We encountered 2 patients with ovarian cancer who developed syndrome of inappropriate antidiuretic hormone secretion (SIADH) after chemotherapy with involved carboplatin. Case 1 was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
(18 reference statements)
0
1
0
Order By: Relevance
“…Syndrome of inappropriate antidiuretic hormone (SIADH) is a disorder in which inappropriate secretion of antidiuretic hormone (ADH) causes hyponatremia ( Yasir and Mechanic, 2022 ). It has been reported that some patients develop SIADH during platinum drug use ( Fujitsuka et al, 2022 ), with carboplatin reported to cause hyponatremia significantly less frequently than cisplatin ( Ezoe et al, 2018 ). There is no clear recommendation regarding measures that should be taken in cases of carboplatin-induced SIADH.…”
Section: Introductionmentioning
confidence: 99%
“…Syndrome of inappropriate antidiuretic hormone (SIADH) is a disorder in which inappropriate secretion of antidiuretic hormone (ADH) causes hyponatremia ( Yasir and Mechanic, 2022 ). It has been reported that some patients develop SIADH during platinum drug use ( Fujitsuka et al, 2022 ), with carboplatin reported to cause hyponatremia significantly less frequently than cisplatin ( Ezoe et al, 2018 ). There is no clear recommendation regarding measures that should be taken in cases of carboplatin-induced SIADH.…”
Section: Introductionmentioning
confidence: 99%